Construção civil e relações geométricas: um caminho para aprender e ensinar matemática? - Rodrigues, José Donizeti (2013)
Mathematics, from the beginning of the schooling process, has occupied important position in the basic training of the citizen, as is present in different activities of our daily life and it is required in almost all selection processes, being so much educational or vocational. Over the past decades, the teaching of Geometry has been neglected in school curricula. An example is the observation that the Geometry is usually work object of the teacher in the classroom only in the last quarter of the year, so when it does not claim lack of time to present it to students, relegating it to oblivion. In addition, many students say that school Mathematics is too theoretical, it has no application in their everyday lives and, consequently, lose interest in studying it and learn it. The research reported here aimed to investigate a strategy didactic and methodological basis for the teaching-learning part of Euclidean Geometry students of 2nd year of high school, a public school in a city in the state of São Paulo. Specifically, the main objective of this research was the development of educational material that exploits mainly the geometric concepts of area, perimeter and scales present in the planning and definition of plant and model of a house from the informal knowledge of the non-professional area, such as masons, carpenters and workmen. Through a sequence of learning activities, originating from problems of construction, sought to integrate motivational elements and creative development of geometrical concepts related to construction the historical elements in the process of teaching and learning. For this was also used in this research plant construction models in the search for ease of viewing and understanding of geometrical concepts studied by students.